Early Cretaceous Volcanic Edifice Activity in the Sulu Orogenic Belt: Evidences From Volcanic-Sedimentary Rhythm Characteristics in Lingshan Island, Eastern Shandong Province, China - Liu, Ruiyang; Zhou, Yaoqi; Dong, Shihui; Zhou, Tengfei; Mu, Hongyu; Bai, Bingyang; Li, Sunyi; Chen, Tongtong; Zhang, Zhenkai (Frontiers in Earth Science, 2022)
A rhyolitic tuff-mudstone interbedded rock outcrop with a good rhythm is found in the Yangjiaodong area of Lingshan Island, eastern Shandong Province. Samples were collected in this study, and the rhythm characteristics were analyzed. The volcanic eruption dynamics process was investigated using the rhythm of volcanic accumulation. The analysis model sets the thickness of the tuffaceous rhyolite layer of the sample to represent the eruption scale, and the thickness of the mud layer represents the dormant time of volcanism. For the deep-time volcanism, the current chronology cannot accurately depict the millennium scales. Therefore, the analysis method of volcanic cycle stratigraphy is undertaken to establish a high-precision magmatic activity time frame related to volcanism and the time-scale sequence analysis of the collected samples is conducted using Acycle software. Combined with the geologic setting of the study area, the parameter deposition rate is the deposition rate of volcanic back-arc basin (6.5m/Ma) with insufficient source supply and the mudstone compaction factor is 0.3. Based on this observation, the thicknesses of different lithologies were counted and the time span of the analyzed sample was calculated to be 2.24Ma, which represents the duration of this eruption event. Signal analysis software performs interpolation, detrending, spectrum analysis, and filtering of quantitative data, obtaining continuous signal curve, which proves that magma chamber is always in an active state over a scale of millennium years. Then, the power spectrum method is used to separate the wave information of continuous signal periods and obtain the activity status of different scales and periods within the magma chamber. It shows cyclicity of 2.296, 5.78,8.475and15.625kyr, and the scales of 2.17,2.94,3.12and18.87m repeatability. Considering that magma eruption is affected by changing melt conditions, the crystallinity, water content, temperature, and pressure are comprehensively considered as “activation conditions” to predict the dynamic process within near-surface magma chamber, which is characterized using a pulsed volcanic eruption model.